Capacity Constraints in Hedge Funds: The Relation between Fund Performance and Cohort Size. Issue 2 (3rd April 2022) - Forsberg, David; Gallagher, David R.; Warren, Geoffrey J.
Abstract: We provide evidence consistent with scale diseconomies for hedge funds being related to the aggregate assets pursing particular investment strategies. This study extends Forsberg, Gallagher and Warren who identified skilled managers with persistent performance by forming peer cohorts of hedge funds using return correlations. Our analysis shows fund performance had a significant negative relation with cohort size, while the relation with fund size is inconsistent across specifications but evident where funds faced limited competition. We also document a weaker relation between performance and inflows where funds faced less competition, suggesting that cohort structure might influence propensity to accept assets.